Moving Toward Zero Waste Cities: A Nexus for International Zero Waste Academic Collaboration (NIZAC) - Hannon, Jonathan; Zaman, Atiq; Rittl, Gustavo; Rossi, Raphael; Meireles, Sara; Palandi, Fernanda Elisa Demore (Springer, 2019)
Waste, is one of the most challenging and complex problems confronting human communities today. Studies indicate that significant improvement in global waste management systems is needed in order to avert a worsening public and environmental health emergency. The global zero waste movement exists within the spectrum of contemporary reaction and response to the growing sense of crisis and urgency around waste issues. The theory of zero waste reconceptualises, waste as a resource, which must be conserved, used efficiently and cycled back into the economic system. Zero waste seeks to assertively redirect the focus of society’s innovation, investment, education, R&D and government, business and community policies and programs away from value destroying ‘burn-bury’ disposal practices. In this sense, zero waste is strategically controversial in challenging society’s dysfunctional and wasteful status quo, as well as the vested interests, which promulgate and profit from this. The international zero waste movement demonstrates alternative approaches, which have a positive track-record of cost effectively addressing waste issues and supporting the innovation required to transition towards a circular economy and more sustainable forms of development. Emerging case studies from within industry, community and city contexts, demonstrate that zero waste approaches are framed in a continuum of learning and evolution and can be successful, scientific, measurable, a good economic investment, socially and culturally beneficial and democratically popular. However, it is also recognised that these positive indicators, are just the precursor of the level of transformational leadership and innovation, which is required in future across spheres such as: policy, programme, technology, education, research and product design, in order to realise the future zero waste city concept. Recognising the phenomenon and positive challenge of zero waste, a cluster of universities/organisations are seeking to catalyse a nexus for international zero waste academic collaboration (NIZAC). The core objective of NZIAC is to facilitate education and research to drive progress towards future zero waste cities, which are critical to realising the concept of a circular global economy and to addressing the interrelated challenges of climate change and sustainable development. A key strand in the discussion and experience informing the development of the NZIAC, is the opportunity of ‘living labs’ research theory and practice to support the co-generation of innovation in a ‘university and host city—community’ context. This paper seeks to provide an overview of relevant research theory, the background experience of project partners, the formative consultation and collaboration process and outcomes to date in exploring the proposed ‘nexus for international zero waste academic collaboration’ (NIZAC).